The Attitudes of Students in Selecting Programs and Places for "Package C" Equivalency Education - Rizqi Nuryanti, Karisma (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This research aims to determine the attitude of the high school students in selecting Package C Equivalency Education Program and PKBM Tirta Pelangi. The research was a case study and was carried out using a qualitative approach. Data collection techniques involved interviews, observation, and documents. The data analysis technique employed discourse analysis. The research results reveal that the learners assess the Package C Equivalency Education Program as a tool to achieve the next goal, problem solver, and a fun school. Moreover, high school students select PKBM Tirta Pelangi because it is a fun and profitable place. Students’ attitude in selecting the Package C Equivalency Education Package C program is that it is used to find jobs and continue students’ education.